Índices físicos de um argissolo manejado com diferentes níveis de intensificação de pastejo de Panicum maximum Jacq. IPR-86 milênio - Guimarães, Renata de (2013)
The expansion of agricultural crops in pastures and appreciation of the cost of land have directed the livestock production systems for more intensive production systems aiming to become the most competitive activity against other land use options . The intensification of grazing is one of the tools used for the intensification of livestock production systems and aims to increase animal productivity per hectare. The adjustment of forage supply coupled with fertilization of soils has been the most used strategy for controlled intensification of grazing, combining individual weight gain to increase the number of animals exploited by area. In this context, the aim of this study was to evaluate the influence of controlled intensification of grazing on a Ultisol in dystrophic layers 0 - 0.10 , 0.10 - 0.20 , 0.20 - 0.30 and 0.30 - 0 40 m conducted in intermittent and variable stocking stocking system. The intensification of grazing increased density, reduced porosity, decreased macroporosity, microporosity increased only in position (ST) without a clump of the 0 - 0.10 m . This reduction in porosity was confirmed by size distribution of pores in which the pores lost greater than 50 µm diameter , but there was an increase of 21µm pores in the surface layer in which the effects of the animal are more trampling intense . Thus, the storage capacity of air (CAT / Pt) shown at position (ST) and a reduction in the most heightened levels, but did not reach the levels considered restrictive. For water retention capacity (CC / Pt) was improved as confirmed by data of the water retention curve with enhanced levels rise further, and results in the sampling position of the clump (CT) through all indices used, had no design changes. This demonstrated the heterogeneity of sampling positions due to the protection that the forage species causes by its caespitose habit of growth. The results showed that, for this class of soil greater availability of forage, attributed to nitrogen fertilization, allowed intensify grazing without compromising the physical quality of the soil studied.